2019
DOI: 10.1007/s13197-019-03758-x
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional biotransformation in traditional fermented tea (Miang) from north Thailand and its impact on antioxidant and antimicrobial activities

Abstract: Miang is a traditional fermented tea made from fermentation of Assam tea leaves with mixed microbial culture involving lactic acid bacteria and yeast. Miang has important bioactive benefits such as antioxidant and antimicrobial activity with relevance to health benefits. Miang is categorized into two processes; filamentous fungi growth-based (FFP) and non-filamentous fungi-based (NFP) process, depending on area of production. Further, Miang is also divided into 2 types; astringent Miang and sour Miang, dependi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 25 publications
4
31
0
Order By: Relevance
“…Some B. tequilensis and B. siamensis isolates showed high acid tolerance, bile salt tolerance, hydrophobicity and antimicrobial activity. Miang may also be considered a traditional fermented product with health-relevant functional benefits with antioxidant compounds such as high levels of phenolic acid and flavonoids [18], which are potentially biotransformed by tannase producing Bacillus spp. Moreover, due to the high numbers of Bacillus spp.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some B. tequilensis and B. siamensis isolates showed high acid tolerance, bile salt tolerance, hydrophobicity and antimicrobial activity. Miang may also be considered a traditional fermented product with health-relevant functional benefits with antioxidant compounds such as high levels of phenolic acid and flavonoids [18], which are potentially biotransformed by tannase producing Bacillus spp. Moreover, due to the high numbers of Bacillus spp.…”
Section: Discussionmentioning
confidence: 99%
“…Until now, there have been few published reports on relevance of endospore-forming bacteria from Miang or other fermented tea leaves products. However, the number of endospore-forming bacteria which accounted for approximately 40-45% of total bacterial counts in 40 Miang samples collected from twenty producing locations were detected and therefore suggested that they play specific roles in Miang fermentation [18].…”
Section: Isolation Of Bacillus Sppmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the chemical complexity of plant extracts, the exact role of major plant components or synergies between plant components still remains in question. However, several clinical studies demonstrated the efficacy of various herbal extracts to reduce plaque deposits and to improve oral conditions such as chronic gingivitis and post-operative dental surgery [39][40][41]44]. The review of literature revealed that vitamins and antioxidants of vegetal origin could interfere with inflammatory reaction, free radicals and endothelin in damaged periodontal tissues [17][18][19]48].…”
Section: Discussionmentioning
confidence: 99%
“…Main natural compounds described as antimicrobial compounds are essential oils (complex mix of terpenoids and phenylpropane derivatives (aromatic compounds)) and tannins (phenolic products that can precipitate proteins, such as escin) [37][38][39][40][41][42]. Some vegetal compounds display anti-inflammatory properties, such as vitamins, mineral elements (iron), proteases (papain and bromelain, a mix of acid proteases), or some flavonoids (close to tannins, such as baicalin) [41,[43][44][45][46]. Vitamins are essential organic substances that are required in small amounts to catalyze metabolic reactions [19].…”
Section: Introductionmentioning
confidence: 99%